Automatic whiteboard cleaner/ Muhammad Idham Abd Aziz ...[et al.] - Abd Aziz, Muhammad Idham; Zainuddin, Muhammad Huzairi; Mohamed Sukor, Nur Maizatul Ashikin; Mohd Zain, Mazratul Firdaus (2018)
Nowadays, whiteboards are widely used in almost every educational institute. About 70-80% educational institute around the world uses whiteboard as the writing medium in their classrooms. They are large size for that reason it is very time consuming process to erase the writings from the board with the duster. As for an hour period of class, about 8-10% of time has waste to just clean the board using the duster. Considering this “Automatic Whiteboard Cleaner”, is an automatic system can solve these problems. The Automatic Whiteboard Cleaner application could reduce the time taken to wipe off the whiteboard as well as reduces the effort to clean the whiteboard. The sensor attached to the Automatic Whiteboard Cleaner acts as the controller in order to operate the automatic Whiteboard Cleaner. The main components of the automatic whiteboard cleaner are Arduino UNO, motion sensor, voltage source and dc motor. Arduino UNO is the core of this project and it is very important to make sure the project can run as expected. If the program gone wrong, it may affect the operation of the motor. The motion sensor is used to detect the movement things. When the motion sensor has detected the movement , it will send the signal to the arduino and it will move the DC motor. The duster will clean the whiteboard automatically. In conclusion, this project will definitely reduce the human’s energy and also will make the work more efficient yet easy from before.